Microanalysis of metal slab used in motorway tunnels to protect concrete and assessment of the state of conservation. (August 2022) - Marrocchino, Elena; Telloli, Chiara; Rimoldi, Sofia; Vaccaro, Carmela
Abstract: The metal slabs studied in this work are used to protect the walls of the motorway tunnels and to improve the lighting conditions inside the tunnel. Their installation causes an increase in the cost of the work, consequently, the coatings must be resistant to corrosion and must not require frequent maintenance in order to be functional for long periods. The material chosen to produce these artifacts is aluminum, but despite this metal being generally resistant to chemical attack, the analyzed coating still suffered corrosion. The sampled and analyzed slab was covered with white titanium-based paint on the side facing the street and a transparent protective resin on the side facing the wall. This preliminary study uses a different approach through microanalysis of metal slabs. For this reason, the corroded slab was studied through different analytical techniques (microscope, SEM-EDS, XRF and Raman analyses) in order to identify the causes of corrosion of the metal slab. The observations made it possible to hypothesize a corrosion process divided into different stages. Graphical Abstract: ga1